![find \: the \: value \: of \: k \: such \:that \\ \: 3 {x}^{2} + 2kx + x - k - 5 \: has \\ \: the \: sum \: of \: zeroes \: as \: half \: of \: their \: product find \: the \: value \: of \: k \: such \:that \\ \: 3 {x}^{2} + 2kx + x - k - 5 \: has \\ \: the \: sum \: of \: zeroes \: as \: half \: of \: their \: product](https://tex.z-dn.net/?f=find+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+k+%5C%3A+such+%5C%3Athat++%5C%5C+%5C%3A+3+%7Bx%7D%5E%7B2%7D+%2B+2kx+%2B+x+-+k+-+5+%5C%3A+has++%5C%5C+%5C%3A+the+%5C%3A+sum+%5C%3A+of+%5C%3A+zeroes+%5C%3A+as+%5C%3A+half+%5C%3A+of+%5C%3A+their+%5C%3A+product)
Answers
Answered by
2
Answer:
Let P(x)=3x
2
+2kx+x−k−5
=3x
2
+x(2k+1)−(k+5)
i.e; ax
2
+bx+c
a=3;b=2k+1;c=−(k+5)
1) Sum of zeroes =
a
−b
=
3
−(2k+1)
2) Product of zeroes =
a
c
=
3
−(k+5)
According to given
−(2k+1)/3=
2
1
[−(k+5)/3]
2(2k+1)=k+5
4k+2=k+5
3k=3⇒k=1
Similar questions